The Impact of Good Corporate Governance on Thai Real Estate Companies’ Firm Performance - Wattanasan, Kanitpirom; Hasan , Kamrul; Lohar, Bhupesh; Cano Garcia, Rosario; Phamonmontri, Chalee (ASEAN Journal of Management & Innovation, 2025)
The purpose of this study was to examine the impact of good corporate governance on Thai real estate companies’ firm performance. This research was quantitative in nature. One respondent from each of the 1,047 registered real estate companies in Thailand made up the population used in this study. A sample size of 285 participants was obtained through the use of simple random sampling. The data collection instrument was a questionnaire created by the researchers. Multiple Regression Analysis, Pearson Product Moment Correlation, VIF, Mean, and S.D. were among the statistical techniques employed in the study. The results showed that: (1) Real estate companies had relatively high levels of corporate governance across all five dimensions. (2) The real estate companies’ firm performance, overall and in both aspects, was at a high level. (3) All corporate governance variables were significantly correlated with firm performance at the 0.01 level, with Pearson Correlation Coefficients (r) ranging from 0.591 to 0.633. (4) The corporate governance dimensions of Integrity (X5), Accountability (X3), and Fairness (X1) had a positive impact on firm performance, with a predictive coefficient of 53.80% (R2 = 0.538). The regression equation in raw scores could be written as: Y = 1.709 + 0.256(X3) + 0.197(X5) + 0.156(X1), and the standardized equation was: Zy = 0.346(X3) + 0.283(X5) + 0.189(X1).